2004
DOI: 10.1113/jphysiol.2003.059246
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological plasticity of GABAA receptors at dentate gyrus synapses in a rat model of temporal lobe epilepsy

Abstract: In the lithium-pilocarpine model (Li-pilocarpine) of temporal lobe epilepsy, GABA A receptormediated inhibitory postsynaptic currents (GABA A IPSCs) were recorded in dentate gyrus granule cells (GCs) from adult rat hippocampal slices. The properties of GABA A IPSCs were compared before and after superfusion of modulators in control conditions (Li-saline rats) and in Li-pilocarpine rats 24-48 h and 3-5 months (epileptic rats) after status epilepticus (SE). The mean peak amplitude of GABA A IPSCs increased by ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
70
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(77 citation statements)
references
References 64 publications
6
70
1
Order By: Relevance
“…In the chronic epilepsy model, multiple subunit mRNA and/or protein changes have been observed days or weeks after SE (Brooks-Kayal et al 1998;Peng et al 2004). It is interesting to note that the alterations of phasic current sensitivity to diazepam and zinc during acute seizures in the present study were similarly observed in epileptic rats (Buhl et al 1996;Cohen et al 2003;Leroy et al 2004). As mentioned earlier, the alterations of allosteric modulation during acute seizures may result from short-term changes in GABA A receptors, whereas those that occur once epilepsy is established may result from long-term changes in GABA A receptors.…”
Section: Seizure-induced Alterations Of Gaba a -Receptor Allosteric Msupporting
confidence: 73%
See 4 more Smart Citations
“…In the chronic epilepsy model, multiple subunit mRNA and/or protein changes have been observed days or weeks after SE (Brooks-Kayal et al 1998;Peng et al 2004). It is interesting to note that the alterations of phasic current sensitivity to diazepam and zinc during acute seizures in the present study were similarly observed in epileptic rats (Buhl et al 1996;Cohen et al 2003;Leroy et al 2004). As mentioned earlier, the alterations of allosteric modulation during acute seizures may result from short-term changes in GABA A receptors, whereas those that occur once epilepsy is established may result from long-term changes in GABA A receptors.…”
Section: Seizure-induced Alterations Of Gaba a -Receptor Allosteric Msupporting
confidence: 73%
“…Diazepam consistently augmented mIPSC amplitude in the present study, which is in contrast with several previous reports that benzodiazepines prolonged the mIPSC decay but did not enhance amplitudes in normal animals (Cohen et al 2003;Leroy et al 2004;Poncer et al 1996). Diazepam modulation of mIPSC amplitude may be age dependent; potentiation of GABA-evoked currents (Zhang et al 2004) and mIPSC amplitudes (Cohen et al 2000;Defazio and Hablitz 1998;Hajos et al 2000;Nusser et al 1997;Perrais and Ropert 1999) has been observed in juvenile neurons including hippocampal dentate granule cells.…”
Section: Seizure-induced Alterations Of Gaba a -Receptor Allosteric Mcontrasting
confidence: 56%
See 3 more Smart Citations